Association of Sugar-Sweetened Beverage Intake with Waist Circumference and Overweight Among Kusuma Husada University Students - Devina, Kezia Elian; Lestari, Puji; Vierdiana, Dyah (Departemen Gizi Masyarakat, Fakultas Ekologi Manusia, IPB dan PERGIZI PANGAN Indonesia, 2026)
Students are one of the groups vulnerable to nutritional problems, including overweight. The increasing availability of sugar-sweetened beverages (SSBs) in shops and cafés has encouraged their consumption among students. SSBs contain added sugars and are generally high in calories, which may contribute to increased body fat, body weight, and waist circumference, thereby increasing the risk of overweight. This study aimed to determine the association between SSB consumption, waist circumference, and overweight among students of the Faculty of Health Sciences, Kusuma Husada University, Surakarta. This analytical observational study employed a cross-sectional design. Data were collected through anthropometric measurements of body weight, height, and waist circumference, as well as a respondent characteristics questionnaire. A Food Frequency Questionnaire (FFQ) was used to assess SSB consumption during the previous month. Data were analyzed using the Chi-square test. The results showed that most participants rarely consumed SSBs, had normal waist circumference, and were not overweight. No significant association was found between SSB consumption and waist circumference (p=0.683) or overweight (p=0.523). In conclusion, SSB consumption was not significantly associated with waist circumference or overweight among students of the Faculty of Health Sciences, Kusuma Husada University, Surakarta.